The Arms Government of a dissident province: a brief narrative of the trajectory of Portuguese major João José da Cunha Fidié in the Independence of Piauí (1822-1823). (Ágora Journal, 2021)
This article seeks, based on a series of empirical data, to build a brief narrative about the passage of the Portuguese Major João José da Cunha Fidié as the Governor of Arms from the Province of Piauí, providing bases for important understandings about the independence period. In contrast to the actions of dissident leaders, such as Simplício Dias, João Cândido and others, we questioned the commitment degree of Fidié's pragmatism in relation to the Portuguese Crown interests, since his presence represented a direct intervention in the political direction of Brazil. For this, we used letters and correspondence from the Overseas Historical Archive and the Ozildo Albano Museum, in order to apprehend the actions and reactions of these subjects, and their contradictions in light of the historical moment analyzed here.